1997
DOI: 10.1152/ajpcell.1997.272.6.c1947
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vascular smooth muscle cell proliferation by plasma membrane Ca(2+)-ATPase

Abstract: We have previously shown that reductions in c-Myb-dependent transcription inhibit cell cycle progression and decrease intracellular Ca2+ concentrations in vascular smooth muscle cells (VSMC). We now report that these effects are largely mediated by a 4- to 10-fold increased rate of La(3+)-sensitive 45Ca extrusion, which is associated with 2- to 4-fold increased levels of plasma membrane Ca(2+)-ATPase 1 (PMCA1) mRNA and protein. PMCA4 mRNA, present at much lower concentrations, undergoes similar changes during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 24 publications
3
63
0
Order By: Relevance
“…Cells were washed twice with phosphate-buffered saline and incubated in Dulbecco's modified Eagle's medium containing 0.25% fetal bovine serum for 48 h at which point the cells were either harvested (G 0 stage cells), or the medium was replaced with Dulbecco's modified Eagle's medium and 10% fetal bovine serum for 8 (G 1 stage cells), 16 (G 1 /S stage cells), or 24 h (G 2 /M stage cells) prior to harvest. The degree and extent of cell cycle synchronization, as assessed by DNA quantitative flow-cytometry, was identical to previously published reports (data not shown) (6,9,10). Primary VSMC were isolated by the method of Cornwell and Lincoln (27) using 10 -12 aortas from C57Bl6 mice (Charles River Laboratories, Inc., Wilmington, MA).…”
Section: Methodssupporting
confidence: 71%
See 3 more Smart Citations
“…Cells were washed twice with phosphate-buffered saline and incubated in Dulbecco's modified Eagle's medium containing 0.25% fetal bovine serum for 48 h at which point the cells were either harvested (G 0 stage cells), or the medium was replaced with Dulbecco's modified Eagle's medium and 10% fetal bovine serum for 8 (G 1 stage cells), 16 (G 1 /S stage cells), or 24 h (G 2 /M stage cells) prior to harvest. The degree and extent of cell cycle synchronization, as assessed by DNA quantitative flow-cytometry, was identical to previously published reports (data not shown) (6,9,10). Primary VSMC were isolated by the method of Cornwell and Lincoln (27) using 10 -12 aortas from C57Bl6 mice (Charles River Laboratories, Inc., Wilmington, MA).…”
Section: Methodssupporting
confidence: 71%
“…These manipulations resulted in a 30% reduction in mean resting [Ca 2ϩ ] i , a 42% decrease in mean S phase entry, and a 36% decrease in the mean cell proliferation rate of synchronized rat VSMC populations (10). We also demonstrated that a direct 2-fold overexpression of PMCA1, independent of any manipulation of c-Myb activity, resulted in similarly significant reduc- tions in [Ca 2ϩ ] i , G 1 to S transitions, and rate of cell proliferation (9). Having demonstrated the physiological importance of PMCA1 regulation in VSMC, we now examine more closely the molecular interaction between c-Myb and the PMCA1 gene.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Removal of extracellular free Ca 2ϩ or blockade of Ca 2ϩ channels inhibits PASMC proliferation (22,26,27,49). Depletion of SR Ca 2ϩ attenuates smooth muscle cell proliferation (25) and promotes apoptosis (50). In contrast, elevated [Ca 2ϩ ] cyt may induce PASMC proliferation by initiating and promoting the cell cycle, and by triggering or promoting gene transcription via transcription factor phosphorylation (21,25,37).…”
Section: Discussionmentioning
confidence: 99%